Estimation Of Biomass Contents And Phytoconstituent Analysis Of Enicostemma Littorale Blume. - R. SATHISHKUMAR; P.T.V. LAKSHMI; A.ANNAMALAI (International Journal of Pharma and Bio Sciences, 2012)
Enicostemma littorale Blume is a medicinal plant commonly called as whitehead. Traditionally, the plant is used in the treatment of large number of human ailments such as in hypoglycemic, lowering the blood glucose level, as a potent anti-diabetic and antioxidant activity. Currently, the scientific research is going on to prove its medicinal value. Hence, to evaluate the phytoconstituents and to estimate the total biomass content of chlorophyll, protein and flavonoid present in the aerial part of the plant has been aimed at. The result shows the presence of protein, flavonoid, carbohydrate, saponins, steroids, alkaloids, etc, and also the significant quantity of chlorophyll and protein in the fresh leaves, and flavonoid in the fresh fruit extracts. Thus, from the result, it has been proved that the plant E.littorale is rich in phytoconstituents and to possesses significant quantity of flavonoid, chlorophyll and protein accompanying its medicinal value.